Developing socio-ecological scenarios: A participatory process for engaging stakeholders - ALLAN, Andrew (Institutional Knowledge at Singapore Management University, 2022)
Deltas are experiencing profound demographic, economic and land use changes and human-induced catchment and climate change. Bangladesh exemplifies these difficulties through multiple climate risks including subsidence/sea-level rise, temperature rise, and changing precipitation patterns, as well as changing management of the Ganges and Brahmaputra catchments. There is a growing population and economy driving numerous more local changes, while dense rural population and poverty remain significant. Identifying appropriate policy and planning responses is extremely difficult in these circumstances. This paper adopts a participatory scenario development process incorporating both socio-economic and biophysical elements across multiple scales and sectors as part of an integrated assessment of ecosystem services and livelihoods in coastal Bangladesh. Rather than simply downscale global perspectives, the analysis was driven by a large and diverse stakeholder group who met with the researchers over four years as the assessment was designed, implemented and applied. There were four main stages: (A) establish meta-framework for the analysis; (B) develop qualitative scenarios of key trends; (C) translate these scenarios into quantitative form for the integrated assessment model analysis; and (D) a review of the model results, which raises new stakeholder insights (e.g., preferred adaptation and policy responses) and questions. Step D can be repeated leading to an iterative learning loop cycle, and the process can potentially be ongoing. The strong and structured process of stakeholder engagement gave strong local ownership of the scenarios and the wider process. This process can be generalised for widespread application across socio-ecological systems following the same four-stage approach. It demands sustained engagement with stakeholders and hence needs to be linked to a long-term research process. However, it facilitates a more credible foundation for planning especially where there are multiple interacting factors.